1985
DOI: 10.1051/forest:19850201
|View full text |Cite
|
Sign up to set email alerts
|

Standing crop, production, and turnover of fine roots on dry, moderate, and wet sites of mature Douglas-fir in western Oregon

Abstract: SummaryStanding crops of live and dead fine (< I mm diameter) and small (1 to 5 mm diameter) roots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
115
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(131 citation statements)
references
References 30 publications
15
115
1
Order By: Relevance
“…The limitations underlined here join the general views (B6hm, 1979;Santantonio and Hermann, 1985), stating how timeconsuming precise root studies can be. An improvement of the methods described here might be to provide for the possibility of taking samples at various precise developmental stages, giving access to studies on root turnover and productivity, and to the study of nutrient cycles.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The limitations underlined here join the general views (B6hm, 1979;Santantonio and Hermann, 1985), stating how timeconsuming precise root studies can be. An improvement of the methods described here might be to provide for the possibility of taking samples at various precise developmental stages, giving access to studies on root turnover and productivity, and to the study of nutrient cycles.…”
Section: Introductionmentioning
confidence: 70%
“…Only a few studies have dealt with adult forest trees, mainly due to the considerable technical problems involved (B6hm, 1979 (Persson, 1983;Santantonio and Hermann, 1985;Ries, 1988). In The method used here is that of regionalized variables developed by Matheron (1965) for prospecting and evaluating geological deposits.…”
Section: Introductionmentioning
confidence: 99%
“…However, this missing biomass should represent a very small part of the total root system biomass. It must also be recalled that fine root biomass may vary all along the year in relation to fine root turnover [21,31]. However, in the study site of Hesse, the data obtained by Epron et al [12] showed that the living fine root biomass varied only slightly during the growing season.…”
Section: Tree Root Biomass and Biomass Incrementmentioning
confidence: 98%
“…The external factors, including temperature, water content, and chemical characteristics of the soil may also control the decay rate of fine roots [22]. Similar mass losses have been reported for fine roots of the Chinese fir (61.3%) after 1 year of decomposition in Huitong north of our research site [15], while much lower values of 12% to 25% were obtained for red pine, Scots pine, Douglas fir, and mixed hardwood in temperate zones [4,11,19].…”
Section: Dry Weight Lossmentioning
confidence: 99%